Moving the Migration Frontier: A Chinese Qiaoxiang Migration Model?. (17th November 2017) - Li, Minghuan; Wong, Diana
Abstract: The New Chinese Migration is frequently contrasted to the earlier 19 th century mass migrations in terms of its origins (urban vs rural), migrant types (students and professionals vs coolies) and destinations (developed vs developing countries). A significant component of this new migration from the PRC however, continues to originate from the qiaoxiang – the emigrant‐sending areas of the 19 th century migrations. Based on an extensive review of the literature on the old and new Chinese migration, as well as several years of fieldwork in the major rural sending areas or qiaoxiang of China, we examine the continuities between the new qiaoxiang migration and the old, and propose a qiaoxiang migration model of the entrepreneurial nature of the migration enterprise to account for the sustained and global character of the mobility generated.